Giải thích các bước giải:
a/. Giả sử: VP = $x^4+4x^3+2x^2-4x+1=(ax^2+bx+c)^2=(x^2+bx+c)(ax^2+bx+c)$ = VT
⇔ $x^4+4x^3+2x^2-4x+1=ax^2(ax^2+bx+c)+bx(ax^2+bx+c)+c(ax^2+bx+c)$
⇔ $x^4+4x^3+2x^2-4x+1=a^2x^4+abx^3+acx^2+abx^3+b^2x^2+bcx-cax^2+bcx+c^2$
⇔ $x^4+4x^3+2x^2-4x+1=a^2x^4+2abx^3+(ac+b^2+ca)x^2+2bcx+c^2$
Để VP đồng nhất với VT thì:
a² = 1
2ab = 4
ac + b² + ca = 2
2bc = - 4
c² = 1
⇒ Có 2 trường hợp:
* a = 1; b = 2; c = - 1
⇒ $x^4+4x^3+2x^2-4x+1=(x^2+2x-1)^2$
* a = -1; b = - 2; c = 1
⇒ $x^4+4x^3+2x^2-4x+1=(-x2-2x+1)^2$
b/. a/. Giả sử: VP = $x^4-6x^3+19x^2-30x+25=(ax^2+bx+c)^2=(x^2+bx+c)(ax^2+bx+c)$ = VT
⇔ $x^4-6x^3+19x^2-30x+25=ax^2(ax^2+bx+c)+bx(ax^2+bx+c)+c(ax^2+bx+c)$
⇔ $x^4-6x^3+19x^2-30x+25=a^2x^4+abx^3+acx^2+abx^3+b^2x^2+bcx-cax^2+bcx+c^2$
⇔ $x^4-6x^3+19x^2-30x+25=a^2x^4+2abx^3+(ac+b^2+ca)x^2+2bcx+c^2$
Để VP đồng nhất với VT thì:
a² = 1
2ab = -6
ac + b² + ca = 19
2bc = - 30
c² = 25
⇒ Có 2 trường hợp:
* a = 1; b = -3; c = 5
⇒ $x^4-6x^3+19x^2-30x+25=(x^2-3x+5)^2$
* a = - 1; b = 3; c = - 5
⇒ $x^4-6x^3+19x^2-30x+25=(-x^+3x-5)^2$
c/. Giả sử: VP = $4x^2+y^2-4xy+8x-4y+4=(ax^2+bx+c)^2=(x^2+bx+c)(ax^2+bx+c)$ = VT
⇔ $(4x^2-4xy+y^2)+4(2x-y)+4=ax^2(ax^2+bx+c)+bx(ax^2+bx+c)+c(ax^2+bx+c)$
⇔ $(2x+y)^2+4(2x-y)+4=a^2x^4+abx^3+acx^2+abx^3+b^2x^2+bcx-cax^2+bcx+c^2$
⇔ $(2x+y)^2+4(2x-y)+4=a^2x^4+2abx^3+(ac+b^2+ca)x^2+2bcx+c^2$
Chúc bạn học tốt